Abitare il limes. Le donne ambulanti della Valcellina - Nadia Boz (Storia delle Donne)
Valcellina is a valley on the extreme western side of the Italian Alps, on the regional border between Friuli and Veneto. In Valcellina there used to be a peculiar form of seasonal migration, historically documented since the 18th century. Towards the end of the 19th century this unique form of migrant labour, based on the door-to-door sale of wooden tools and other locally made artifacts, became markedly genderized and was practiced mainly by women who would travel seasonally along a network of exchanges reaching all over northern Italy and across the national borders. This essay aims to retrieve the history and features of this peculiar seasonal migration on the basis of archival research and oral contributions, thereby exploring its emancipatory effects on the women who undertook it.